Continuing the diversity journey : business practices, perspectives and benefits (Luxembourg, 2008)
"Many companies are rapidly realising that the promotion and management of workplace diversity can be a vital strategic resource for competitive advantage, not only for multinationals but also for SMEs, supporting organisations and bodies concerned with business education and promotion. This publication – written for the Directorate-General for Employment, Social Affairs and Equal Opportunities – therefore brings together surveys analysing issues relating to diversity and the ways companies seek to respect and promote diversity in the workplace. The overall goal of this publication is to provide guidance and support to companies that are at different stages in the implementation of diversity in the workplace, and it is intended for businesses of all sizes, business support organisations and business schools."